Ceramic figures : a directory of artists - Flynn, Michael, 1947- (New Brunswick, NJ : Rutgers University Press, 2003)
Presents a collection of alphabetically arranged entries that provide a look at the most innovative figurative ceramic artists of the late twentieth century and illustrates a variety of each artists work.
Adult
Keywords: Potters -- Directories; Pottery figures; Potters -- Directories; Pottery